1985
DOI: 10.3109/10915818509014502
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis Quantitation of Type 2 Cells and Alveolar Walls Part II: Influence of 0.3 ppm Nitrogen Dioxide Exposure on the Developing Mouse Lung

Abstract: Newborn male mice (45 control and 45 experimental) were tested after 6 weeks of 0.3 ppm nitrogen dioxide (NO,) exposure and at postexposure periods of 4 and 10 weeks. After 6 weeks of exposure, there was a 12.9% increase in type 2 cell number that was statistically significant (P < 0.025) and an 11% increase in mean type 2 cell area that fell short of statistical significance. The ratio of cell area to alveolar wall area was also statistically significant ( P = 0.05). The latter ratio, dividing a combined meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…While confirmatory and additional data are needed for definitive conclusions, the findings are in accord with prior animal studies where ambient levels of NO, and/or 0, have been shown to alter alveolar epithelial cells and alveolar walls Richter, 1982, 1986;Sherwin et al, 1983aSherwin et al, , 1985. The same kinds of alterations were found in this study on comparing mice exposed to the Los Angeles atmosphere with a matched group in Santa Barbara, that is, greater numbers of Type 2 cells (p -.05), larger Type 2 cells (total cell area per lung field as well as mean area per cell, p = .01 and p -.06, respectively), and more alveolar wall area (p < .OOl).…”
Section: Commentssupporting
confidence: 89%
See 1 more Smart Citation
“…While confirmatory and additional data are needed for definitive conclusions, the findings are in accord with prior animal studies where ambient levels of NO, and/or 0, have been shown to alter alveolar epithelial cells and alveolar walls Richter, 1982, 1986;Sherwin et al, 1983aSherwin et al, , 1985. The same kinds of alterations were found in this study on comparing mice exposed to the Los Angeles atmosphere with a matched group in Santa Barbara, that is, greater numbers of Type 2 cells (p -.05), larger Type 2 cells (total cell area per lung field as well as mean area per cell, p = .01 and p -.06, respectively), and more alveolar wall area (p < .OOl).…”
Section: Commentssupporting
confidence: 89%
“…The investigation is an extension of earlier studies where mice had been exposed to ambient levels of nitrogen dioxide (NO,) and/or ozone (03) and lung alterations were detected, in particular increases in numbers and size of Type 2 cells and increases in the amount of alveolar wall area. Since the large volume measurements provided by image analysis were sufficiently sensitive to detect the effects of ambient levels of NO, (Sherwin and Richters, 1982;Sherwin et al, 1985) and O3 (Sherwin and Richters, 1986;Sherwin et al, 1983a), it seemed likely that the complex of air pollutants in community atmospheres would also cause detectable alterations of the lung.…”
Section: Introductionmentioning
confidence: 97%
“…Comparable increases were found in the earlier study of the adult mouse exposed to ozone (Sherwin et al, 1983) and following NO 2 exposure of both adult and newborn mice (Sherwin and Richters, 1982;Sherwin et al, 1985). Furthermore, an 11% increase (p = 0.07) in "non-cellular interstitium" occurred when young adult rats were exposed to 0.25 ppm ozone (Barry et al, 1983).…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, since ozone-induced type II cell hyperplasia tends to predominate in the proximal acinus of the lung (Boorman et al, 1980;Eustis et al, 1981;Chow et al, 1981), there has very likely been an accentuation of the masking effect-i.e., "crowding" of type II cells in a localized area facilitates cell abutment. As cited in an earlier report (Sherwin et al, 1985), type II cell hyperplasia following hyperoxia and superambient NO 2 exposure can lead to total replacement of the alveolar lining by type II cells. There are also structural differences between the newborn and adult lung that may facilitate cell abutment, in particular an incomplete expansion of alveoli in the developing lung (Thurlbeck, 1975).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation